The Ideal of Beauty and Harmony in the European Fine Art - Demianchuk, Andrii L.; Stelmashchuk, Halyna H.; Babunych, Yuliya I.; Krotova, Tetyana F.; Gakh, Iryna S.; Honcharuk, Oleksandr V. (The journal of contemporary issues in business and government, 2021)
As a higher form of mastering the world following the laws of beauty, the best works of the European art do not just bring in some aesthetic pleasure but also help to understand (and create) the beautiful. In this research, using comparative, typological, descriptive, visual, philosophical, theological, and artistic analysis methods an analysis of the selected pieces, from the ancient times till present was made. It was traced that the ideal of beauty and harmony largely depended on the peculiarities of each historical period. Development of spiritual culture of the European continent nations underwent many stages: from primitive art through the ancient times and till modernism. In each period fixed rules and norms shaped up the ideal of beauty and harmony, which can be understood only through immersing into a certain epoch via analysis and study of a specific piece of art. Scientific novelty of the results obtained lies in the fact that materials about the ideal of beauty and harmony in the aesthetics of the European art are added to art criticism as universal general human values. The ideal of beauty and harmony over the whole historical period, as exemplified by preserved monuments, can be traced in all art forms, in particular, in sacral art.